The Influence of Entrepreneurship Education on Work Motivation and Entrepreneurial Career Intentions for Students on Vocational Education - Geria, Anak Agung Oka; Agung, Anak Agung Gede; Gading, I Ketut; Parwata, I Gusti Lanang Agung (Migration Letters, 2023)
The aim of the research is to determine and explain entrepreneurship education on work motivation and entrepreneurial career intentions among Bali Tourism Polytechnic students. This quantitative research method involved 2,556 students, then samples were taken based on Morgan’s theory which was corrected by Warwich and Lininger, and 392 people were obtained. Hypothesis testing using Structural Equation Modeling with Partial Least Squares. The research results are; (1) entrepreneurship education has a positive and significant direct effect on work motivation, shown in the coefficient value of 0.251, T-statistics 2.428 and P-Values 0.016; (2) Entrepreneurship education has a positive and significant direct effect on entrepreneurial career intentions, shown in the coefficient value of 0.107, T-Statistics 2.057 and P-Values 0.042; (3) Work motivation has a direct positive and significant effect on entrepreneurial career intentions with a coefficient value of 0.468, T-Statistics 5.868 and P-Values 0.000; (4) entrepreneurship education has an indirect effect on entrepreneurial career intentions through work motivation shown in the coefficient value of 0.118, T-Statistics 2.055 and P-Values 0.040. This research found that work motivation has the strongest direct influence on entrepreneurial career intentions, besides that it can also mediate the influence of entrepreneurship education on entrepreneurial career intentions. It is recommended to increase entrepreneurial career intentions among vocational higher education students by involving work motivation as a mediating variable.